Automatic identification of two-word terms in English text. - Heng, Siok Tian. (2008)
The study compares the effectiveness of two statistical formulae, mutual information and contextual information formulae, for identifying collocations or two-word terms in English text. A modified version of the contextual information formula was found to perform better than mutual information.